ANALISIS LAPORAN KEUANGAN DALAM MENILAI KINERJA KEUANGAN PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN KUPANG - Tiffany N. P. Gah; Ferdyan Tallo Manafe (JAKA - Jurnal Jurusan Akuntasi, 2022)
This research was conducted with the aim of knowing the Financial Performance of the Regional Financial and Asset Management Agency of Kupang Regency. In this study, the method used is descriptive quantitative, where the data source consists of secondary data obtained from data collection through observation, interviews and document or library studies. This study uses financial statement analysis in assessing financial performance The technical analysis of the data used is descriptive quantitative with the formula: Fiscal Decentralization Degree Ratio, Regional Financial Independence Ratio, PAD Effectiveness Ratio, Regional Financial Efficiency Ratio, Harmony Ratio and Growth Ratio. The results of the analysis show that the Regional Financial Performance of Kupang Regency is seen from (1) the Ratio of the Degree of Fiscal Decentralization is still very low because the average ratio is 6.79%, (2) the Regional Financial Independence Ratio is still very low and belongs to the instructive pattern because the average the average is only 7.92%, (3) the PAD Effectiveness Ratio can be categorized as less effective because the average ratio is 81.4%, (4) the Regional Financial Efficiency Ratio is categorized as efficient because the average ratio is 96.40%, (5) The Harmony Ratio can be said that the Kupang Regency Government allocates most of its budget for regional operating expenditures, which is 74.80% compared to capital expenditures of 13.84% and (6) Growth Ratio of PAD, Revenue, Operational Expenditures and Capital Expenditures has decreased from year to year